A trans-umbilical single-site plus one robotic-assisted surgery for choledochal cyst resection in children - Lin, Yucan; Chen, Shan; Lin, Yang; Zhang, Ling; Wang, Jianbin; Qiu, Xinyi; Xu, Di; Li, Lizhi (Frontiers in Pediatrics, 2024)
The purpose of this study was to compare the intraoperative and postoperative outcomes of trans-umbilical single-site plus one robot-assisted and trans-umbilical single-site laparoscopic in the treatment of choledochal cysts.2 Methods: We retrospectively analyzed clinical data from 49 children diagnosed with choledochal cysts admitted to our hospital from June 2020 to December 2023. Among these patients, 24 underwent trans-umbilical single-site plus one Da Vinci robot-assisted surgery(the robot group) and 25 underwent trans-umbilical single-site laparoscopic-assisted surgery(the laparoscopic group). We compared differences in intraoperative and postoperative outcomes between the two groups.Results: There was no significant difference between the two groups in terms of gender, age, weight, clinical symptoms, maximum cyst diameter, type, postoperative complications, and FLACC scoring between the two groups (p > 0.05). Compared with the laparoscopic group, the patients in the robot group had less intraoperative bleeding [10 (8, 12) vs 15 (11.5, 18) ml, p<0.001], less postoperative drainage tube indwelling time [5 (4, 6) vs 7 (5.5, 8) day, p< 0.001], less postoperative fasting time [4 (3, 4) vs 6 (5, 7) day, p< 0.001] and less Postoperative hospitalization time[6 (6, 7) vs 8 (6, 10) day, p< 0.001], but more operative time [385.5 (317.0, 413.3) vs 346.0 (287.0, 376.5) min, p=0.050] and more hospitalization expenses (79323±3124 vs 31121±2918 yuan, p< 0.001).The results of this study showed shorter hospitalization time, quicker postoperative recovery, and less tissue damage, but the higher cost and the longer operation time in patients who chose robot surgery than laparoscopic surgery. With the continuous expansion of the installed scale of robot-assisted surgery systems and the gradual accumulation of surgeons' technical experience, robot-assisted surgery may slowly surpass and has a trend to replace laparoscopy for its advantages.